Immunoglobulin M Response Post DBL2Β-PFEMP1 Recombinant Protein Injection in Wistar Rats: Study for Malaria Vaccine Development - Erma Sulistyaningsih; Achmad Faza Abdillah; Rosita Dewi; Sheilla Rachmania (Al-Kauniyah: Jurnal Biologi, 2026)
Vaccination is vital in malaria prevention strategies. The DBL2β-PfEMP1 recombinant protein is a malaria vaccine candidate due to its essential role in severe pathogenesis. This study analyzed the IgM levels after DBL2β-PfEMP1 recombinant protein injection. This study used nineteen male Wistar rats, aged 2–3 months, and was divided into a control group, which was injected with NaCl 0.9%, and four treatment groups, which were injected with DBL2β-PfEMP1 protein in doses of 150 μg without adjuvant, and 150, 300, and 450 μg with adjuvant. Rats were injected subcutaneously twice at a 6-week interval. Blood samples were collected two weeks after injection. IgM was measured using the ELISA. There was an increasing trend in IgM levels after the DBL2β-PfEMP1 protein injection with a dose-dependent effect in the primary injection. The One-way ANOVA test showed a significant difference between groups (p = 0.037), and the post-hoc Bonferroni test showed a significant difference only between a control and treatment group of 450 μg + adjuvant (p= 0.046). A trend of increasing IgM in secondary injection was only observed in the 150 μg + adjuvant group, which is suggested as an optimum dose. Further analysis of other immune indicators is needed to draw a comprehensive immune response in developing a malaria vaccine candidate.